A two-echelon supply chain model with price and warranty dependent demand and pro-rata warranty policy under cost sharing contract - Samanta, Biswarup; Giri, Bibhas Chandra (Decision Making: Applications in Management and Engineering, 2021)
In this article, a two-echelon supply chain model with a single-vendor a single-buyer is considered. The vendor’s production process is imperfect and the market demand is assumed to be dependent on the buyer’s selling price and warranty period. The vendor consents to return a definite portion of the buyer’s purchase value, if any product is found defective within the length of warranty. The refund value or the warranty cost is considered as a function of the warranty period and the buyer’s selling price of the item. This warranty cost is assumed to be fully borne by the vendor in the first model (Model I) while in the second model (Model II), it is assumed that the buyer agrees to bear a portion of the warranty cost. The proposed models are solved under decentralized scenario. We also derive and optimize the average total profit of the supply chain in order to obtain the optimal decisions of the centralized model. We consider a Stackelberg game between the vendor and the buyer in the decentralized scenario, where the vendor is assumed to be the leader and the buyer as the pursuer. Through numerical study, it is observed that, with respect to all the key decisions of the models, Model II provides better outcomes than Model I. Sensitivity analysis is also carried out to examine the impacts of changes of parameter-values on the optimum decisions.